Coffee Consumption and Mortality Among US Adults: A Cohort Study. (29th May 2020) - Zhou, Bingjie; Bhupathiraju, Shilpa; Ruan, Mengyuan; Chui, Kenneth; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Coffee is a commonly consumed beverage in the United States (US). It remains controversial whether coffee consumption is associated with health benefits or harms, especially when cream and/or sugars are added. Methods: We assessed coffee consumption in association with mortality outcomes among 36, 758 US adults ages 20+ years who participated in the National Health and Nutrition Examination Survey (NHANES) 1999–2014. Consumption of total, caffeinated, and decaffeinated coffee, with and without additives, was assessed using dietary data collected from 24-hour diet recalls (24HR) and compared to coffee consumption assessed using a food-frequency questionnaire (FFQ). Mortalities from all causes, heart disease, and cancer were obtained from linkage to the National Death Index through December 31, 2015. We used Cox proportional hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) after multivariable adjustments. Results: The mean (SE) of the total, caffeinated, and decaffeinated coffee consumption among US adults was 1.36 (0.02), 1.19 (0.02), and 0.17 (0.004) cups/day, respectively. The Spearman correlation coefficient on coffee consumption for a subset of participants with both 24HR and FFQ is 0.78 ( P -value < 0.0001). During a median follow-up of 7.4 years, a total of 4662 deaths occurred due to all causes, including 794 deaths due to heart disease and 1019 deaths due to cancer. Compared to individuals who were not usual coffee drinkers (<1 cup/d), those who drank coffee for 1 cup/day or more had a lower risk of all-cause mortality (HR [95% CI]: 0.84 [0.76, 0.94] for ≥1 to <2 cups/d; 0.82 [0.72, 0.92] for ≥2 to <3 cups/d; and 0.80 [0.68, 0.93] for ≥3 cups/d; P-trend = 0.001]. Adding milk/cream, alone or with sugar/sweetener, did not significantly change the results. Similar patterns were observed for caffeinated coffee consumption and all-cause mortality, but no significant associations were found for decaffeinated coffee. Coffee consumption was not significantly associated with cancer or heart disease mortality except that moderate caffeinated coffee consumption (≥1 to <2 cups/d) was significantly associated with a lower risk of heart disease mortality [HR (95% CI): 0.72 (0.52, 0.98)]. Conclusions: Usual coffee consumption was associated with a reduced risk of all-cause mortality among US adults. Funding Sources: NIH/NIMHD.